Evolution of land use and vegetation cover in the pioneering subwatershed "Conservador das Águas" project (2006-2018) - Cruz, Tatiana Cardoso da; Coletta, Luciana Della; Lacerda, Camila Souza dos Anjos; Santos Junior, Wilson Messias dos (Revista Agrogeoambiental, 2020)
In this study, we evaluated the spatial-temporal changes in three subwatersheds essential for the hydrodynamics of Jaguari River (Ribeirão das Posses, Forjos and Saltos) after the implementation of the “Conservador das Águas” project in the municipality of Extrema (MG). We used satellite images from TM-Landsat-5 from year 2006 and OLI-Landsat-8 from year 2018 to map land use and vegetation cover, and the SPRING software to classify images in Geographic Information Systems (GIS) and quantify the occurrence of the classes analyzed in 2006 and 2018. After these analyses, we observed 19,77% increase in vegetation cover in the three subwatersheds. Surprisingly, we also detected a similar result in adjacent subwatersheds where the project was not implemented. Thus, this study suggests a positive effect of the “Conservador das Águas” project to the maintenance of biodiversity and hydric system functioning of that region, resulting in increased environmental quality standards and effectiveness of the environmental services for the community and its properties.